Wife rape : understanding the response of survivors and service providers - Bergen, Raquel Kennedy (Sage Publications, 1996)
With expertise and sensitivity, the author of this accessibly written volume addresses a real but long-neglected problem: the pain and humiliation of sexual assault suffered by many women at the hands of their partners. Extensive gathering of personal testimony from survivors, together with interviews with service providers, bears witness to a lack of validation and insufficient assistance currently available for such women. This volume gives hope to survivors and provides critical information for service providers to gain a better understanding of the seriousness of the problem.